The relationship between pregnant women's knowledge of nutrition and efforts to prevent stunting in children at Wijaya Kusuma Hospital - Siti Urifah; Maulana Maulana (PT WIM Solusi Prima, 2026)
Pregnancy is a natural process, but if it is not properly monitored throughout the period, early detection of complications in the mother and fetus can be missed. Additional calories and other nutrients are essential to meet the mother's nutritional needs, support fetal growth and development, and provide energy for the birth process. Stunting prevalence: According to UN Statistics (2020), 149 million toddlers worldwide suffer from stunting, and 6.3 million of them are in Indonesia. The 2022 Indonesian Nutritional Status Survey (SSGI) recorded a national stunting rate of 21.6%, with a target of reducing it to 14% by 2024. This study aims to determine the relationship between pregnant women's knowledge about nutrition and the prevention of stunting in children at Wijaya Kusuma Hospital, Lumajang Regency. The type of research used is observational analytical research. The research design used is a cross-sectional survey. The research design used was a cross-sectional survey. The study population was pregnant women visiting the RSWK Obstetrics and Gynecology clinic. A sample of 60 respondents according to the inclusion and exclusion criteria. Data collection was carried out using interview methods and filling out questionnaires. The analysis was then conducted using the chi-square test. Table 1 shows that the majority of the 60 respondents, 46.7%, had an elementary/junior high school education. Table 2 shows that 25% of the 60 respondents had good knowledge of pregnancy. So it can be concluded that most pregnant women have poor knowledge about nutrition during pregnancy. Poor knowledge about pregnancy nutrition is caused by the majority of pregnant women's education level in this study being at the elementary level (elementary school, junior high school).